Design and Synthesis of Inductorless Passive Cell Operating as Stop-Band Negative Group Delay Function - Mathieu Guerin (IEEE, 2021)
This paper develops an original circuit theory of unfamiliar stop-band (SB) negative group delay (NGD) topology. The proposed NGD topology is implemented without inductor component. The developed theory is established with passive cell constituted by RC-network based high-pass (HP) and low-pass (LP) NGD composite circuits. The analytical investigation of the SB-NGD circuit is introduced from the elaboration of voltage transfer function (VTF). The canonical form enabling to identify SB-NGD circuit is analytically expressed. The different SB-NGD characteristics as GD value, and, center and cut-off frequencies are innovatively formulated in function of the circuit resistor and capacitor components. The existence condition of SB-NGD function is also established. The inductorless SB-NGD topology is validated by a proof-of-concept (POC) circuit implemented by surface-mounted-device (SMD) component based printed circuit board (PCB). The measured VTF magnitude and group delay (GD) are extracted from the experimented S-parameters. A good agreement between the calculated, simulated and measured results is obtained. The SB-NGD behavior has measured center frequency of about 32 MHz. The lower- and upper-NGD cut-off frequencies are about 9.15 MHz and 98.3 MHz. The optimal NGD values at low and higher frequencies are −3.25 ns and −56 ps.